Users, User-Friendliness and Projected Uses of Isichazamazwi SesiNdebele: An Analysis - Khumalo, Langa (Lexikos, 2009)
Abstract: This article discusses the first-ever monolingual general Ndebele dictionary, Isichazamazwi SesiNdebele (henceforth the ISN) within the context of the history of lexicography and the compilation of dic-tionaries in Ndebele. It further assesses the scope of the dictionary with regard to its structure. It also dis-cusses decisions taken by the editors during the writing of the ISN in an attempt to compile a user-friendly dictionary primarily aimed at secondary schools and the general Ndebele population. The assumptions of the editors, coming from a non-existing lexicographic tradition, were mainly based on their experiences and intuitions as Ndebele mother-tongue speakers, educators and language practitioners. The article also ac-counts for four major uses of the dictionary.